Do more, spend less ebook The new secrets of living the good life for less. - Wilson, Brad (2013)
Achieve stellar savings with the techniques used on bradsdeals.com Do More, Spend Less provides tips, advice, real-world examples, and strategies consumers need to know to compete in the consumer world. Author Brad Wilson, founder of BradsDeals.com, explains the techniques and buying strategies that are used on his site, which have saved 19 million consumers more than $200 million on BradsDeals.com in the past year alone. The majority of deals on his site provide free, or nearly free, products and services. This book provides tips, advice, real-world examples, and strategies consumers need to know to compete in the consumer world. Shares why you should never buy an Apple product from the Apple store Details how to spend three weeks in a suite at the Park Hyatt Paris for $20 Shares the unknown way to clean up your credit report and add at least 20 points to your score The entire basis for thinking about how best to shop, spend, travel, bank—essentially all aspects of being a consumer—has fundamentally changed. The power is now in your hands, and Do More, Spend Less shows you how to master your savings.